Diaphragm material for lithium battery and preparation method of diaphragm material
By introducing modified nano-TiO2 composite materials into the lithium-ion battery separator to form a three-dimensional network structure, the problem of easy curling of the ceramic coating in a dry environment is solved, the liquid absorption and ionic conductivity of the separator are improved, and the stability and mechanical properties of the battery are improved.
Patent Information
- Application Number
- CN202511041147.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-10-03
AI Technical Summary
Ceramic coatings are susceptible to dry environments during the assembly of lithium-ion batteries, causing the separator to curl and affecting battery cell production efficiency and yield.
Modified nano-TiO2 composite materials are introduced into the separator to form a three-dimensional network structure, improve liquid absorption and ionic conductivity, and enhance mechanical properties.
It improves the liquid absorption and ionic conductivity of the separator, improves the cycle stability and rate performance of the battery, reduces the interfacial impedance, and enhances the thermal stability and mechanical properties.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and more particularly to a diaphragm material for lithium batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries, with their advantages of high specific energy, long cycle life, and no memory effect, are widely used in a wide range of fields, including new energy vehicles, aerospace, and military applications. As a crucial component of lithium-ion batteries, the separator acts as an electronic insulator between the positive and negative electrodes, while also ensuring the free movement of ions. While the separator does not directly participate in the battery's electrochemical reactions, its structure and performance play a significant role in the battery's cycle life, safety, energy density, and power density.
[0003] Because ceramic coatings contain hydrophilic groups such as hydroxyl groups, they readily absorb or lose water in humid or dry environments. During lithium-ion battery assembly, dry conditions can cause the ceramic coating to lose water, which in turn creates tensile stress on the base film, causing the separator to curl toward the coating, thereby impacting cell production efficiency and yield. Summary of the Invention
[0004] The present invention provides a lithium battery diaphragm material and a preparation method thereof. By adding a modified nano-TiO2 composite material and introducing nanoparticles into the diaphragm, a three-dimensional network structure is formed, thereby improving the liquid absorption and ionic conductivity of the diaphragm. At the same time, the diaphragm has high air permeability and good mechanical properties and ionic conductivity.
[0005] In a first aspect, the present invention provides a diaphragm material for a lithium battery, comprising a base film and a modified nano-TiO2 coating, wherein the modified nano-TiO2 coating is arranged on at least one side surface of the base film, and the modified nano-TiO2 coating comprises the following raw materials in parts by weight: 55 to 80 parts of a modified nano-TiO2 composite material, 8 to 24 parts of a binder, and 2.5 to 7.5 parts of a dispersant; the modified nano-TiO2 composite material is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as a raw material; the mass ratio of the cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium is 1-5:2-3:1.
[0006] Preferably, the preparation method of the modified nano-TiO2 composite material comprises the following steps: S1: Dispersing cellulose nanocrystals in water, adding nano-TiO2 suspension, with the mass ratio of cellulose nanocrystals to nano-TiO2 being 1:3-5, and ultrasonically treating to prepare a composite; S2: preparing lanthanum zirconate loaded with rare earth praseodymium by ion doping method; S3: dispersing the composite in ethanol, adding lanthanum zirconate loaded rare earth praseodymium powder, ultrasonically treating, dropping tetrabutyl titanate, stirring to form a gel, and drying to obtain a modified nano-TiO2 composite material.
[0007] Preferably, the base membrane is a polyolefin microporous membrane.
[0008] Preferably, the binder includes a soft monomer and a hard monomer, the soft monomer includes acrylates, the hard monomer includes one or more of (meth)acrylonitrile, acrylonitrile, styrene, and (meth)acrylates, and the molar ratio of the soft monomer to the hard monomer is 1.5-6.3.
[0009] Preferably, the dispersant is one or more of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate and ammonium polyacrylate.
[0010] Preferably, the composition further comprises a wetting agent and a thickening agent, wherein the wetting agent is a silicone nonionic surfactant and the thickening agent is sodium hydroxymethyl cellulose.
[0011] In a second aspect, the present invention provides a method for preparing a lithium battery separator material, comprising the following steps: (1) Weighing the raw materials by weight, dissolving the binder in N-methylpyrrolidone, adding the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mixing and dispersing in a ball mill, and obtaining a nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side surface of the base film, dried and rolled up to prepare a lithium-ion battery separator.
[0012] Preferably, the thickness of the nano-TiO2 composite material coating on one side is 2.0-5.0 μm.
[0013] In a third aspect, the present invention provides a lithium-ion battery comprising the lithium battery diaphragm material.
[0014] In summary, the present invention has the following beneficial effects: The modified nano-TiO2 composite material of the present invention is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers, with nano-TiO2 as the raw material. Cellulose nanocrystals are rich in surface hydroxyl groups. Chemical modification (such as esterification, etherification, or silanization) can introduce hydrophobic groups or polymer chains, thereby improving their dispersibility and compatibility in hydrophobic polymers. Cellulose nanocrystals are biodegradable and renewable, making them an environmentally friendly alternative to traditional fossil-based polymers, reducing their environmental impact. Cellulose nanocrystals serve as a carrier or template, inducing the synthesis of mesoporous TiO2, increasing its specific surface area and porosity, thereby enhancing its photocatalytic performance. Lanthanum zirconate serves as a dopant, modifying the TiO2 lattice structure and inhibiting its transition to the rutile phase, thereby improving its photocatalytic activity. Similar to lanthanum, as a rare earth element, praseodymium doping can also enhance the photocatalytic activity of TiO2. Cellulose nanocrystals act as structural modulators to optimize the morphology and pore structure of TiO2, while lanthanum zirconate and rare earth praseodymium act as dopants to improve its electronic structure and light absorption properties. The three work synergistically to further enhance the photocatalytic efficiency and stability of nano-TiO2.
[0015] 2. The high specific surface area and porous structure of the nano-TiO2 in the modified nano-TiO2 composite material of the present invention can significantly reduce the transmission resistance of electrons and lithium ions, thereby improving the conductivity of the electrode material and the lithium ion diffusion rate. The porous structure and high specific surface area of nano-TiO2 can increase the contact area between the electrode material and the electrolyte, thereby reducing the charge transfer resistance and improving the reversible insertion and extraction ability of lithium ions. Nano-TiO2 has a positive impact on the electrochemical performance of lithium battery separators by increasing ionic conductivity, enhancing electrochemical stability, improving mechanical properties, optimizing liquid absorption and porosity, enhancing cycle stability and rate performance, and reducing interfacial impedance.
[0016] 3. The nano-TiO2 composite system of the present invention introduces nanoparticles into the separator, forming a three-dimensional network structure that improves the separator's liquid absorption and ionic conductivity. The nano-TiO2 surface undergoes a Lewis acid-base interaction with carbonates and other components in the electrolyte, promoting the dissociation of Li⁺, thereby forming an interfacial phase enriched in "free" Li⁺ at the particle / electrolyte interface and increasing the Li⁺ transport rate. Through grafting modification, the nano-TiO2 forms active sites on the separator surface, enhancing the separator's wettability and thermal stability. This modification significantly improves the thermal stability, ionic conductivity, and mechanical properties of lithium battery separators, thereby enhancing the battery's cycling stability and rate capability.
[0017] It should be understood that the above general description and the following detailed description are merely exemplary and explanatory and are not intended to limit the scope of protection of the present invention. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below with reference to the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions were carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0019] Example Example 1 A lithium battery separator material comprises a base film and a modified nano-TiO2 coating, wherein the modified nano-TiO2 coating is arranged on at least one surface of the base film, and comprises the following raw materials in parts by weight: 55 parts of a modified nano-TiO2 composite material, 8 parts of a binder, 2.5 parts of a dispersant, 3 parts of a wetting agent, and 1 part of a thickener; the modified nano-TiO2 composite material is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as a raw material; the mass ratio of cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium is 5:2:1.
[0020] The preparation method of the modified nano-TiO2 composite material comprises the following steps: S1: Disperse cellulose nanocrystals in water, add nano-TiO2 suspension, the mass ratio of cellulose nanocrystals to nano-TiO2 is 1:5, and ultrasonicate to prepare a composite; S2: preparing lanthanum zirconate loaded with rare earth praseodymium by ion doping method; S3: dispersing the composite in ethanol, adding lanthanum zirconate loaded rare earth praseodymium powder, ultrasonically treating, dropping tetrabutyl titanate, stirring to form a gel, and drying to obtain a modified nano-TiO2 composite material.
[0021] The base film is a polyolefin microporous film; the binder comprises a soft monomer and a hard monomer, the soft monomer comprises acrylic esters, the hard monomer comprises (meth) acrylonitrile, and the molar ratio of the soft monomer to the hard monomer is 1.5.
[0022] The dispersant is sodium polyacrylate; the wetting agent is a silicone nonionic surfactant; and the thickener is sodium hydroxymethyl cellulose.
[0023] A method for preparing a lithium battery diaphragm material, comprising the following steps: (1) Weighing the raw materials by weight, dissolving the binder in N-methylpyrrolidone, adding the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mixing and dispersing in a ball mill, and obtaining a nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side of the base film, the thickness of the nano-TiO2 composite material coating on one side is 2.0 μm, and the base film is dried and rolled up to prepare a lithium-ion battery separator.
[0024] Example 2 A lithium battery separator material comprises a base film and a modified nano-TiO2 coating, wherein the modified nano-TiO2 coating is arranged on at least one surface of the base film, and the modified nano-TiO2 coating comprises the following raw materials in parts by weight: 65 parts of a modified nano-TiO2 composite material, 18 parts of a binder, 5 parts of a dispersant, 4 parts of a wetting agent, and 2 parts of a thickener; the modified nano-TiO2 composite material is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as a raw material; the mass ratio of cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium is 3:2:1.
[0025] The preparation method of the modified nano-TiO2 composite material comprises the following steps: S1: Disperse cellulose nanocrystals in water, add nano-TiO2 suspension, the mass ratio of cellulose nanocrystals to nano-TiO2 is 1:3, and perform ultrasonic treatment to prepare a composite; S2: preparing lanthanum zirconate loaded with rare earth praseodymium by ion doping method; S3: dispersing the composite in ethanol, adding lanthanum zirconate loaded rare earth praseodymium powder, ultrasonically treating, dropping tetrabutyl titanate, stirring to form a gel, and drying to obtain a modified nano-TiO2 composite material.
[0026] The base film is a polyolefin microporous film; the binder includes a soft monomer and a hard monomer, the soft monomer includes acrylic esters, the hard monomer includes (meth) acrylonitrile, and the molar ratio of the soft monomer to the hard monomer is 2.5.
[0027] The dispersant is sodium polyacrylate; the wetting agent is a silicone nonionic surfactant; and the thickener is sodium hydroxymethyl cellulose.
[0028] A method for preparing a lithium battery diaphragm material, comprising the following steps: (1) Weighing the raw materials by weight, dissolving the binder in N-methylpyrrolidone, adding the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mixing and dispersing in a ball mill, and obtaining a nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side of the base film, and the thickness of the single-side nano-TiO2 composite material coating is 3.5 μm. The base film is dried and rolled up to prepare a lithium-ion battery separator.
[0029] Example 3 A lithium battery separator material comprises a base film and a modified nano-TiO2 coating, wherein the modified nano-TiO2 coating is arranged on at least one surface of the base film, and comprises the following raw materials in parts by weight: 80 parts of a modified nano-TiO2 composite material, 24 parts of a binder, 7.5 parts of a dispersant, 5 parts of a wetting agent, and 3 parts of a thickener; the modified nano-TiO2 composite material is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as a raw material; the mass ratio of the cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium is 5:2:1.
[0030] The preparation method of the modified nano-TiO2 composite material comprises the following steps: S1: Disperse cellulose nanocrystals in water, add nano-TiO2 suspension, the mass ratio of cellulose nanocrystals to nano-TiO2 is 1:4, and ultrasonicate to prepare a composite; S2: preparing lanthanum zirconate loaded with rare earth praseodymium by ion doping method; S3: Dispersing the composite in ethanol, adding lanthanum zirconate loaded rare earth praseodymium powder, ultrasonically treating, dropping tetrabutyl titanate, stirring to form a gel, and drying to obtain a modified nano-TiO2 composite material.
[0031] The base film is a polyolefin microporous film; the binder includes a soft monomer and a hard monomer, the soft monomer includes acrylic esters, the hard monomer includes (meth) acrylonitrile, and the molar ratio of the soft monomer to the hard monomer is 6.3.
[0032] The dispersant is sodium polyacrylate; the wetting agent is a silicone nonionic surfactant; and the thickener is sodium hydroxymethyl cellulose.
[0033] A method for preparing a lithium battery diaphragm material, comprising the following steps: (1) Weighing the raw materials by weight, dissolving the binder in N-methylpyrrolidone, adding the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mixing and dispersing in a ball mill, and obtaining a nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side of the base film, and the thickness of the nano-TiO2 composite material coating on one side is 5.0 μm. The base film is dried and rolled up to prepare a lithium-ion battery separator.
[0034] Comparative Example 1 The difference from Example 1 is that no modified nano-TiO2 composite material is added.
[0035] Comparative Example 2 The difference from Example 1 is that the modified nano-TiO2 composite material is replaced by nano-TiO2.
[0036] Comparative Example 3 The difference from Example 1 is that no cellulose nanocrystals are added to the modified nano-TiO2 composite material.
[0037] The performance test of lithium battery separator was carried out. The needle puncture strength and thermal shrinkage of lithium battery separator were tested with reference to GB / T36363-2018. The obtained data are as follows: Table 1 Performance test results The data in Table 1 show that the separators prepared in Examples 1-3 of the present invention exhibit good needle punch strength, excellent electrolyte wettability, low thermal shrinkage, and good thermal stability. This demonstrates that the addition of the modified nano-TiO2 composite material, by introducing nanoparticles into the separator to form a three-dimensional network structure, improves the separator's liquid absorption and ionic conductivity. Furthermore, the separator exhibits high air permeability, good mechanical properties, and good ionic conductivity.
[0038] The foregoing description is merely an exemplary embodiment of the present invention, and the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.
Claims
1. A lithium battery separator material, characterized in that: The invention comprises a base film and a modified nano-TiO2 coating, wherein the modified nano-TiO2 coating is arranged on at least one side surface of the base film, and the modified nano-TiO2 coating comprises the following raw materials in parts by weight: 55-80 parts of a modified nano-TiO2 composite material, 8-24 parts of a binder, and 2.5-7.5 parts of a dispersant; the modified nano-TiO2 composite material is prepared using cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium as modifiers and nano-TiO2 as a raw material; and the mass ratio of the cellulose nanocrystals, lanthanum zirconate, and rare earth praseodymium is 1-5:2-3:
1.
2. The lithium battery separator material according to claim 1, characterized in that The preparation method of the modified nano-TiO2 composite material comprises the following steps: S1: Dispersing cellulose nanocrystals in water, adding nano-TiO2 suspension, with the mass ratio of cellulose nanocrystals to nano-TiO2 being 1:3-5, and ultrasonically treating to prepare a composite; S2: preparing lanthanum zirconate loaded with rare earth praseodymium by ion doping method; S3: dispersing the composite in ethanol, adding lanthanum zirconate loaded rare earth praseodymium powder, ultrasonically treating, dropping tetrabutyl titanate, stirring to form a gel, and drying to obtain a modified nano-TiO2 composite material.
3. The lithium battery separator material according to claim 1, wherein: The base film is a polyolefin microporous film.
4. The lithium battery separator material according to claim 1, characterized in that The binder includes a soft monomer and a hard monomer. The soft monomer includes acrylates, and the hard monomer includes one or more of (meth)acrylonitrile, acrylonitrile, styrene, and (meth)acrylate. The molar ratio of the soft monomer to the hard monomer is 1.5-6.
3.
5. The lithium battery separator material according to claim 1, characterized in that: The dispersant is one or more of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate and ammonium polyacrylate.
6. The lithium battery separator material according to claim 1, characterized in that: The invention also comprises a wetting agent and a thickening agent, wherein the wetting agent is a silicone alcohol nonionic surfactant and the thickening agent is sodium hydroxymethyl cellulose.
7. The method for preparing a lithium battery separator material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Weighing the raw materials by weight, dissolving the binder in N-methylpyrrolidone, adding the modified nano-TiO2 composite material, dispersant, wetting agent and thickener, mixing and dispersing in a ball mill, and obtaining a nano-TiO2 composite material coating slurry; (2) The nano-TiO2 composite material coating slurry is coated on one side surface of the base film, dried and rolled up to prepare a lithium-ion battery separator.
8. The method for preparing a lithium battery separator material according to claim 7, wherein: The thickness of the nano-TiO2 composite material coating on one side is 2.0-5.0 μm.
9. A lithium-ion battery, characterized in that: The lithium battery separator material comprises the lithium battery separator material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Lithium battery diaphragm as well as preparation method and application thereof
CN116565456A
Ceramic modified lithium battery diaphragm and preparation method thereof
CN119208902A
Nanometer coating liquid, preparation method thereof and nanometer coating diaphragm
CN120310342A
Cited By
Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device
CN122177935A
Battery cells and their preparation methods, battery devices, power consumption devices and energy storage devices
CN122177935B
